Representación social del paciente que se beneficia de la interacción universidad pública y hospitales generales - Borghi, Wanilda Maria Meira Costa [UNESP]; Sundefeld, Maria Lúcia Marçal Mazza [UNESP]; Saliba, Nemre Adas [UNESP] (My University, 2007)
Hospitals are very important for the health system. The objective of this quali-quantitative research was to visualize patients' social representation, which profited of the interaction between public universities and hospitals. 105 patients in the waiting rooms at the Integrated Clinic at FOA _ UNESP in the first semester 2005 answered to the question: How did you know about the service at FOA? - in opened interviews, recorded or written. A collective speech of the subject represented the field that allouds a society to speak as one. Twenty three of all patients have been sent to FOA by Health Assistance Centers in Araçatuba (7) and region (16) and twenty one patients assisted in Araçatuba by emergency. We can observe that the interaction between the public universities and general hospitals is a reality.
The social representation of the patient who profits from the interaction between public universities and general hospitals
Keywords: Deontological assistance; General hospitals; Oral health; Patients; Universities